Nutritional therapy and caloric achievement within the first week of PICU admission - Melia Yunita; Desy Rusmawatiningtyas; Titis Widowati (Paediatrica Indonesiana, 2018)
Background Nutritional therapy is an important aspect in managing PICU patients. Careful decisions should be made regarding initiation, route of administration, and achievement based on caloric requirements. Many conditions could affect the application of nutritional therapy. Objective To investigate the implementation of nutritional therapy during the 1st week after PICU admission. Methods We conducted a retrospective study involving 156 children aged 1 month-18 years who were hospitalized for at least 4 days in the PICU during the period of January 1st, 2015 toÂ December 31st, 2015. Subjects were divided into three groups according to initiation time of caloric administration, which were: category I (within the first 24 hours of PICU admission), category II (within the first 25-48 hours of PICU admission), and category III: (more than 48 hours after PICU admission). Caloric requirement was calculated using the Caldwell or Schofield formula, whilst caloric achievement was figured up from PICU daily monitoring sheets containing nutritional therapy given to the subjects. Results Of 131 subjects, 72 (55%) had good nutritional status and 59 (45%) children had malnutrition. Caloric administration was initiated within 24 hours of admission in 101 (77.1%) patients, of whom 90 (89.1%) patients received enteral feeding. Nineteen (14.5%) patients received their initial calories within 25-48 hours of admission, with 16 (84.2%) using the enteral route. At the 4th and 7th days of hospitalization, 93 (71%) and 107 (81.7%) patients achieved >70% of their caloric requirements. Delays in feeding initiation were due to shock, gastrointestinal bleeding, inotropic support, and feeding intolerance, which reduced caloric achievement. Conclusion Most patients receive nutritional therapy in the first 48 hours after PICU admission and achieve >70% of their caloric requirements at the 4th day of hospitalization. The enteral route is preferred. Delayed initiation of nutritional therapy reduce caloric achievement.